SURROGATE MOTHER;TINJAUAN HUKUM PERDATA DAN ISLAM - Selian, Muhammad Ali Hanafiah (Jurnal Yuridis, 2017)
In the national law context, surrogate mother or populary and the term often used is ?womb renting? is defined freely as an agreement between a woman who bind themself with another party (husband or wife) to become pregnant with the result of conception of the husband and wife that planted into her womb. Womb renting is a condition of a woman that contracted or hired to raise a fetus that belong to other woman or other spouse. On the other hand, the surrogate mother in Islam, commonly called al-?Ummu al-musta?jin or al-?Ummu al-badilah or also known as ar-rahmu al-musta?jin. In the implementation womb renting involves two parties, the first party is a woman that rent her womb and the second party that rent the womb who have no offspring. The price of rent according to an agreement between the parties.